2005
DOI: 10.1177/1087057104269731
|View full text |Cite
|
Sign up to set email alerts
|

Highly Miniaturized Formats for In Vitro Drug Metabolism Assays Using Vivid® Fluorescent Substrates and Recombinant Human Cytochrome P450 Enzymes

Abstract: Highly miniaturized P450 screening assays designed to enable facile analysis of P450 drug interactions in a 1536-well plate format with the principal human cytochrome P450 enzymes (CYP3A4, 2D6, 2C9, 2C19, and 1A2) and Vivid ® fluorogenic substrates were developed. The detailed characterization of the assays included stability, homogeneity, and reproducibility of the recombinant P450 enzymes and the kinetic parameters of their reactions with Vivid ® fluorogenic substrates, with a focus on the specific character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 37 publications
0
56
0
Order By: Relevance
“…Although microsomal assays are commonly used to evaluate the activity of P450 enzymes, fluorescent methods for determining P450 activity allow for high-throughput screening and more reproducible results [21][22][23][24][25] . Bell et al found that nearly 75% of marketed drugs yielded acceptable correlations between fluorogenic and HLM+LC-MS/MS assays for CYPs 3A4, 2D6, and 2C9, which supports the use of fluorogenic assays for rapid early risk binning based on IC 50 values [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Although microsomal assays are commonly used to evaluate the activity of P450 enzymes, fluorescent methods for determining P450 activity allow for high-throughput screening and more reproducible results [21][22][23][24][25] . Bell et al found that nearly 75% of marketed drugs yielded acceptable correlations between fluorogenic and HLM+LC-MS/MS assays for CYPs 3A4, 2D6, and 2C9, which supports the use of fluorogenic assays for rapid early risk binning based on IC 50 values [26] .…”
Section: Discussionmentioning
confidence: 99%
“…The assays were performed according to the manufacturer's recommendations (20). The incubation times were chosen according to the CYP and CYP substrate combination, as described earlier (21). For CYP2D6 and its substrate Vivid 2D6 cyan, the fluorescence was recorded every minute between 0 to 60 min after the start of the assay.…”
Section: Methodsmentioning
confidence: 99%
“…These products can then be detected directly using a fluorescence plate reader. This method has the advantage that it is a fast and cost-effective way to perform thousands of IC 50 determinations per year (3,4). Measurements may be subject to interference from test inhibitors which either fluoresce or cause fluorescence quenching.…”
Section: In Vitro Methodologiesmentioning
confidence: 99%